Effects of girdling on growth, flower formation, and nut quality of Juglans sigillata - Da Yuan; Wen’e Zhang; Dong Huang; Jian Peng; Alagie Njie; Xuejun Pan (Cogent Food & Agriculture)
Juglans sigillata Dode is a unique walnut species in China that is widely distributed in southwestern China. This study investigated the effects of different girdling degrees on tree growth, flower bud differentiation, fruit quality, and leaf physiology using high-grafting 5-year-old ‘Qianhe 7’ walnuts as test material. Results showed that girdling 3/4 turn increased the proportion of medium and short branches, female flower bud differentiation (1.62 times higher than ungirdling), and fruit set rate (by 11.18%). It also improved fruit weight, diameter, and nutritional content (protein and fat). Girdling increased N content in branches but reduced Ca, Mg, and Fe. Leaf N, Ca, Mg, and Mn contents decreased, while organic carbon and C/N ratio increased. Chlorophyll content and net photosynthesis rate declined. Concurrently, there was an elevation of promoting flower hormones (ZR, ABA) in leaves and female flower buds, while inhibiting flower hormone (GA3). Therefore, it can be inferred that girdling jointly regulates walnut flower bud differentiation and fruit set through modulation of nutrient supply, photosynthesis, and hormone signaling pathways. New shoots stop growing for a week, making 3/4 turn girdling can effectively promote the flower bud differentiation and fruit set of J. sigillata.